Evaluating single nucleotide polymorphisms in beta - 2 - microglobulin – a theoretical study - Daoud, Ammar K.; Alqarqaz, Wafa’ A.; Al Okor, Majduleen M. (Frontiers in Immunology, 2025)
BackgroundIn Immunology, many molecules are composed of Immunoglobulin domains. Beta 2 Microglobulin (B2M) is the smallest Immunoglobulin Domain Superfamily member composed of a single domain that is highly conserved in nature in all vertebrates with low rate of Single Nucleotide Polymorphisms (SNP).ObjectiveWe wanted to mathematically evaluate the effects of the SNP’s-induced Amino Acid (AA) substitutions on the primary structure of the protein.MethodsA C++ computer program code was written to take the 360 B2M mature DNA nucleotide sequences giving back the corresponding protein sequence of 119 AA. For each nucleotide the corresponding 3 possible SNP’s were generated and the 9 possible modifications per triplet were assessed, taking into consideration critically located AA’s like Cysteine residues involved in disulfide bond formation and the formation of Stop Codons. We used Sneath Score for resemblance of chemical structure to further evaluate the AA Substitutions.ResultsIn 22.1% of SNP’s no change in the resulting AA was seen, and in 25.4% of cases a relatively small change was seen with an AA of the same group (Positively Charged, Negatively Charged, Polar, Special and Hydrophobic AA). In 5.3% of the cases, a Stop codon was generated which will lead to an early catastrophic termination of the DNA transcription process. Most cases of SNP’s (47.2%) involve a relatively big change characterized by the substitution by an AA of a totally different chemical group leading to a possibly significant result.ConclusionsThe occurrence of SNP’s in B2M is an important “random” event that can affect the structure of the protein. We attempted to evaluate the effect of SNP’s on the primary structure of B2M and concluded that there is need to improve the computer software programs evaluating the effect of SNP’s and other genetic modifications on the proteins as well as improving the scoring systems evaluating the AA substitutions.